(untitled) (The Macau Ricci Institute Journal, 2023)
Changing China may seem at first sight a most absurd enterprise, given how its cultural patterns seem so deeply entrenched in the strongly hierarchical traditions characteristic of the “Middle Kingdom”. Nevertheless, this view ignores the fact that China and especially its wisdom and ethical traditions are in a constant process of change, as they often are revised to achieve social progress. As Zhou Shoujin documents, one of the most important of these events was the May Fourth New Culture Movement which started in 1919. This movement had a profound impact in China related to its belief that science and democracy, nicknamed “Mister Sai” (science) and “Madame De” (democracy), will eventually transform China’s cultural traditions. In the Republican era the question was whether the moral imperatives of the Confucian “Junzi”, the morally refined person, would simply be replaced by some Western approach to science and democracy or if there could be a synthesis between the ancient wisdom traditions, accommodating a democratic and scientific worldview. China’s traditional ethos based on the hierarchical structure of legitimate moral authority was thus enriched by an awakening of awareness of the pluralism of civilizations and a sincere desire for genuine dialogue among civilizations.